2020
DOI: 10.3390/rs12061028
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Derived PM2.5 Composition and Its Differential Effect on Children’s Lung Function

Abstract: Studies of the association between air pollution and children’s health typically rely on fixed-site monitors to determine exposures, which have spatial and temporal limitations. Satellite observations of aerosols provide the coverage that fixed-site monitors lack, enabling more refined exposure assessments. Using aerosol optical depth (AOD) data from the Multiangle Imaging SpectroRadiometer (MISR) instrument, we predicted fine particulate matter, PM 2.5 , and PM 2.5 speciation concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…On the other hand, model performance in the U.A.E. was similar to the improved results we found modeling PM 2.5 and PM 2.5 speciation over California [29], which incorporated meteorology. We observed that the non-linear relationship between PM 2.5 and satellite-retrieved AOD also affected the predictive performance of machine learning methods differently: gradient boosting, random forest, and support vector machines performed better than ridge and LASSO regression.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…On the other hand, model performance in the U.A.E. was similar to the improved results we found modeling PM 2.5 and PM 2.5 speciation over California [29], which incorporated meteorology. We observed that the non-linear relationship between PM 2.5 and satellite-retrieved AOD also affected the predictive performance of machine learning methods differently: gradient boosting, random forest, and support vector machines performed better than ridge and LASSO regression.…”
Section: Discussionsupporting
confidence: 78%
“…We used a selection of five different machine learning models [29,38] in a regression framework (LASSO regression, ridge regression, gradient boosting machines (GBM), random forests (RF), and support vector machines (SVM)) [39]. In previous studies, non-linear methods (GBM, RF, and SVM) demonstrated stronger predictive performance compared to linear learners (LASSO and ridge), due to the non-linear relationship between PM 2.5 and satellite-observed AODs [29,38,40]. We considered linear methods to assess whether the pattern of non-linearity held in this region with more extreme climate conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite-derived PM 2.5 concentration and composition estimates were proven to be related to respiratory disorders (children's lung function) [28]. This demonstrates the possibility of overcoming the limits due to the discontinuity of the information provided by ground stations, both in space and time, using remotely sensed products.…”
Section: Introductionmentioning
confidence: 83%